Energy and exergy analyses of a novel solar PTC assisted multi-generation system. (2019) - Bamisile, Olusola O.; Dagbasi, Mustafa; Abbasoglu, Serkan
In this study, a solar assisted multi-generation system is presented. The exergy and energy performance analyses are the objective of this research. The multi-generation system consists of two Rankine cycles, two absorption cycles and a hot water tank. Solar parabolic trough collectors are used to generate thermal energy from the Sun which in turn is used to power the system. The multi-generation system achieves an energy and exergy efficiency of 77% and 49%, respectively without solar input. Considering the solar PTC, the efficiencies respectively are 57% for energy and 40% for exergy. The COPs for the absorption cycle and other findings from the study are presented in details in the full paper. Exergy destruction in major components is calculated and parametric studies are done to check the performance of the system under varying global solar irradiance conditions.